Auriculoterapia na Atenção Primária à Saúde como prática de cuidado às mulheres no climatério - Dourado, Ana Karoline Macedo (2025)
The Climacteric is defined by the World Health Organization as a biological phase in a woman's life that encompasses the transition from the reproductive to the non-reproductive period. Care for women during this period should be expanded, and discomforts should be addressed in different ways, not just with hormone therapy. Integrative and Complementary Practices in Health, with a focus on auriculotherapy, emerge as an auxiliary option for managing clinical manifestations during this phase. Objectives: To describe the perceptions of women who use auriculotherapy in Primary Health Care about the clinical manifestations of menopause; To understand the perceptions of women and health professionals who use auriculotherapy in Primary Health Care to manage the clinical manifestations of menopause; To develop an auriculotherapy guide for managing the clinical manifestations of menopause. This is a Convergent Care Research (CCR) conducted in a Family Health Unit in a municipality in the metropolitan region of Salvador, with 12 women aged 40 to 65, experiencing transient clinical manifestations, who were linked to the unit, and 5 health professionals with higher education or technical training, with over 6 months of service in the unit. Data collection took place between April and June 2024 through discussion circles, semi-structured interviews, and conversations, according to the research phases: conception, instrumentation, scrutiny, and analysis. The empirical material was organized and analyzed based on Bardin’s method. As research results, two manuscripts were produced. The first discusses how climacteric manifestations negatively affect women's well-being. The second addresses the positive perceptions of women regarding the use of auriculotherapy for managing the climacteric, with a reduction in the frequency and/or intensity of the symptoms experienced, leading to improvements in self-esteem and well-being. It also highlights the perceptions of health professionals about the importance of strengthening integrative and complementary practices in public health and including auriculotherapy in women’s health care during the climacteric. As a technical product, a model guide for auriculotherapy in managing clinical manifestations of the climacteric is presented, which serves as a tool for planning, implementing, and evaluating auriculotherapy practice in women's health care. The CCR emphasized the need to discuss this topic and create listening spaces where women can share their experiences and health needs. Expanding the availability of care practices for this group, such as auriculotherapy, should be considered in Primary Health Care to enable comprehensive care for women’s health.